Assessment of winter hardiness and decorative properties of introduced juniper varieties in the conditions of the of Nur-Sultan city (Eurasian Journal of Ecology, 2022)
Activities to enrich the species diversity of ornamental conifers contribute to the improvement of aesthetic, sanitary conditions and the solution of ecological problems of the urban environment. The article presents data on the study of species composition and evaluation of juniper varieties introduced in the Astana Botanical Garden in 2018-2021. The purpose of this work is to evaluate the winter hardi-ness and ornamental properties of various forms of juniper in the botanical garden for the subsequent landscaping of the region. Five forms of the genus Juniperus L. (J. pseudosabina Fisch. & C. A. Mey, J. sa-bina L., J. x pfitzeriana (Spath) P.A. Schmidt., J. horizontalis, J. scopulorum Sarg.) planted in the opening year of the botanical garden in order to determine the decorative and optimally adaptive characteristics that characterize the prospects for growing plants in urban plantings. Conclusions on an adaptation of species to climatic and soil conditions of Nur-Sultan city are made and recommendations on successful introduction of some juniper varieties under the analyzed conditions are given. Based on a comprehen-sive assessment, recreational-aesthetic and weather-resistant varieties of the Nur-Sultan are identified J. sabina L., J. x pfitzeriana and J. horizontalis, recommended for use in landscaping, while J. pseudosabina and J. scopulorum rock juniper require additional care. Key words: Juniper, variety, evaluation, assessment, adaptability, decorativeness.